Clinicopathologic features, treatment, and prognosis of pregnancy-associated breast cancer - Li, Yuechong; Wang, Yingjiao; Sun, Qiang; Shen, Songjie (Frontiers in Oncology, 2022)
Purpose: To identify the clinicopathological features, treatment, and prognosis of patients with breast cancer, who were diagnosed during and after pregnancy. Methods: We searched for patients with pregnancy-associated breast cancer (PABC) using the big data query and analysis system of Peking Union Medical College Hospital from between January 1, 2013, and December 31, 2021, and matched each patient with two non-PABC patients by age at diagnosis, year at diagnosis, and tumor stage. The clinicopathologic features, treatment, and outcomes of breast cancer during pregnancy (BC-P) and breast cancer during the first-year post-partum (BC-PP) were examined retrospectively in two case-control studies. Results: Eighteen BC-P cases, 36 controls for BC-P cases, 62 BC-PP cases, and 124 controls for BC-PP cases were enrolled in our study. The expression of HER-2 and Ki-67 was higher in BC-PP cases than in its controls (P=0.01, 0.018, respectively). Patients with BC-PP were more likely to choose mastectomy than breast-conserving surgery (P=0.001). There were no significant differences in event-free survival (EFS) between patients with BC-P and BC-PP and their controls. Conclusion: BC-P and BC-PP patients displayed adverse clinicopathological features in our population. However, when matched by age at diagnosis, year of diagnosis, and tumor stage, BC-P and BC-PP patients did not show inferior outcomes to controls, probably due to aggressive multimodality therapy.